Pengaruh Media Sosial Facebook dan Youtube terhadap Pembentukan Budaya “Alone Together” - Irsa Bastian; Abdul Kholik; Raveal Ono Jayama (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2022)
The development of digital communication technology has drastically transformed human interaction patterns, especially through social media platforms like Facebook and YouTube. While digital connectivity has increased, a paradoxical phenomenon known as alone together has emerged, where increased online interaction is accompanied by a decline in face-to-face communication. This study aims to analyze how the intensity of Facebook and YouTube usage influences the formation of alone together culture among students at Sekolah Tinggi Agama Buddha (STAB) Nalanda. A quantitative approach with an explanatory survey design was used, and a sample of 100 respondents was selected using proportionate stratified random sampling. Data were collected through a 5-point Likert scale questionnaire and analyzed using multiple linear regression. The results revealed that both Facebook (β = 0.41; p < 0.05) and YouTube (β = 0.37; p < 0.05) significantly influence the alone together culture, with a combined contribution of 62% (R² = 0.62). These findings support the Uses and Gratifications theory, which suggests that social media use can fulfill communication needs but also create a paradox where online connections rise while face-to-face closeness declines. The study underscores the importance of digital literacy in balancing social media usage with direct interpersonal interaction, ensuring that communication quality is maintained while minimizing the negative effects of alone together